Optimalisasi Pemanfaatan Teknologi dalam Administrasi Desa Melalui Program Kerja KKN Pelatihan Administrasi Perangkat Desa di Desa Essang, Talango, Sumenep - Rahman, Bohri; Taembo, Maulid; Mujtahidin, Mujtahidin; Thahirah, Iqlima; Syaifuddin, Muhammad; Putri, Triana Rofika (Yayasan Arrahman Nahdlatul Wathan, 2024)
The enactment of regional government law number 32 of 2004 has had a major impact on the structure of village government. To run village government effectively, efficient administrative arrangements are crucial. Regulation of the Minister of Home Affairs Number 47 of 2016 stipulates the framework of village administration, covering general affairs, population, finance, development, and village deliberative bodies. However, the lack of understanding of computer technology in Essang Village, Sumenep Regency prompted the KKN 27 team to hold a village administration training program with a participatory approach. The method used was to conduct participatory training and mentoring for village staff and officials in several activities including counseling and preparation of practical guidebooks. The results of this activity were an increase in the skills of village officials in using computer technology for village governance. Thus, there was efficiency and transparency in village administration in Esang, Talango District, Sumenep Regency.